Penetapan Upah dan Struktur Skala Upah dalam Undang-Undang Cipta Kerja: Analisis Kritis Perspektif Ibn Khaldun - Nabilla Umroh Yuliatul Korida; M. Muhsin (Jurnal Antologi Hukum, 2021)
This study aims to find out how changes in wage policy in the Job Creation Act No. 11 of 2020 is seen from the perspective Ibn Khaldun's theory of wages. There are three discussions, namely: 1) How provisions for determining the minimum wage in the Job Creation Act No. 11 of 2020, 2) What are the provisions on the structure and scale of wages in the Law Job Creation Law No. 11 of 2020, 3) How are the components and determination wages in the Job Creation Law No. 11 of 2020. Types of research used is library research, then the data is obtained from documentation which is then drawn to conclution objectively and systematically in a context, do the research results have similarities or the difference between the rule of law and Ibn Khaldun's theory. Could concluded that, 1) Determination of the minimum wage in the Job Creation Act different from Ibn Khaldun's wage theory, namely the Job Creation Law based on economic and labor conditions and take into account the value of KHL, while Ibn Khaldun is based on the ability / skill or workload that is owned by workers. 2) Determination of the structure and scale of wages in the Copyright Law Work according to Ibn Khaldun's theory of wages, namely the ability/skill of the workers become one of the factors in determining wages. 3) While in wage determination there are similarities between Ibn Khaldun and the job creation law because it is based on demand and supply or production results. Penelitian ini bertujuan untuk mengetahui bagaimana perubahan kebijakan pengupahan dalam UU No 11 Tahun 2020 tentang Cipta Kerja dilihat dari perspektif teori upah Ibn Khaldun. Terdapat tiga pembahasan, yaitu: 1) Bagaimana ketentuan penetapan upah minimum dalam Undang-Undang No 11 tahun 2020 tentang Cipta Kerja, 2) Bagaimana ketentuan struktur dan skala upah dalam Undang-Undang No 11 tahun 2020 tentang Cipta Kerja, 3) Bagaimana komponen dan penetapan upah dalam Undang-Undang No 11 tahun 2020 tentang Cipta Kerja. Jenis penelitian yang digunakan adalah penelitian pustaka, maka data diperoleh dari dokumentasi yang kemudian ditarik kesimpulan secara objektif dan sistematis dalam suatu konteks, apakah hasil penelitian memiliki persamaan atau perbedaan antara peraturan undang-undang dengan teori Ibn Khaldun. Dapat disimpulkan bahwa, 1) Penetapan upah minimum dalam UU Cipta Kerja berbeda dengan teori upah Ibn Khaldun yaitu UU Cipta Kerja berdasar pada kondisi ekonomi dan ketenagakerjaan serta memperhitungkan nilai KHL, sedangkan Ibn Khaldun mendasar pada kemampuan/skill atau beban kerja yang dimiliki para pekerja. 2) Penetapan struktur dan skala upah dalam UU Cipta Kerja sesuai dengan teori upah Ibn Khaldun yaitu kemampuan/skill para pekerja menjadi salah satu faktor dalam penetapan upah.3) Sedangkan dalam penetapan upah ada persamaan antara Ibn Khaldun dengan UU Cipta kerja karena didasarkan pada permintaan dan penawaran atau hasil produksi.